PENGELOLAAN SUMBERDAYA PESISIR BERBASIS MASYARAKAT (PBM) MELALUI AWIG-AWIG DI LOMBOK TIMUR DAN SASI DI MALUKU TENGAH - Setiyono, Edi (Sabda: Jurnal Kajian Kebudayaan, 2016)
Community Based Management (CBM) makes people as the one who has a main role in the natural resource management. This management involves local people in planning, executing and also enjoying the result of that natural resource management. The basic principle of SBM is the government empowers the potency of local wisdom available in an area and make it as the principle of the coastal resource management. CBM can be seen in Awig-Awig Tradition in East Lombok and Sasi Tradition in Middle Maluku. Awig-Awig is a convention of East Lombok people. This convention becomes a written traditional law legalized by Village Regulation containing rules to regulate coastal resource management along with the sanction if it is broken. Awig-Awig is highly obeyed by East Lombok people that makes it suitable for empowering local people to manage their natural resources. Meanwhile, Sasi tradition on in Middle Maluku can be simply described as prohibition and license of catching fish in a certain period. As Awig-Awig in East Lombok, Sasi is also legalized by the traditional law and has sanction for those who break the law. These two traditions, Awig-Awig Tradition in East Lombok and Sasi Tradition di Middle Maluku, are both aimed at preserving the natural resources so that it can be the basic principle in Coastal Resources Community Based Management.